2022
DOI: 10.21613/gorm.2022.1342
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Fractalkine Concentrations in Pregnancies Complicated by Fetal Growth Restriction

Abstract: OBJECTIVE: Fractalkine is a newly discovered chemokine that is expressed in placental tissue during pregnancy and is subsequently shed into the maternal serum. Although there are a few studies examining the relationship between fractalkine and preeclampsia, its role in isolated fetal growth restriction has not been investigated yet. In this study, we aimed to investigate the relationship between isolated fetal growth restriction and maternal serum fractalkine concentrations. STUDY DESIGN: This cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recent studies revealed that FKN might contribute to endometrial receptivity, implantation, and pregnancy (Kervancioglu Demirci et al, 2016; Machairiotis et al, 2021; Pap et al, 2020; Toprak Sager et al, 2022). It has also been described that FKN can modulate the inflammatory action of macrophages by altering the production of proinflammatory cytokines (Gong et al, 2021; Pandur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that FKN might contribute to endometrial receptivity, implantation, and pregnancy (Kervancioglu Demirci et al, 2016; Machairiotis et al, 2021; Pap et al, 2020; Toprak Sager et al, 2022). It has also been described that FKN can modulate the inflammatory action of macrophages by altering the production of proinflammatory cytokines (Gong et al, 2021; Pandur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…FKN level is elevated in the first trimester in the first trimester of pregnancy, but at high concentrations, it may associate with preeclampsia [41], although the serum level of FKN cannot be used as a prediction marker for preeclampsia [42]. Maternal serum FKN level may contribute to pregnancy complications like fetal growth restriction [43]. On the other hand, decreased expression of FKN in granulosa cells may contribute to elevated apoptosis and may be involved in abnormal oocyte maturation in patients with polycystic ovarian syndrome [44].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that FKN is involved in the development of endometrial receptivity and embryo implantation, and it has a role in pregnancy [ 23 ], although its role in pregnancy is not fully understood [ 24 , 25 , 26 ]. In addition, it has been described that FKN may act as a regulator of iron metabolism in macrophages, microglia and endometrium cells [ 8 , 27 ].…”
Section: Introductionmentioning
confidence: 99%